Different Teams, Same Conclusions? A Systematic Review of Existing Clinical Guidelines for the Assessment and Treatment of Tinnitus in Adults - Fuller, Thomas E.; Haider, Haula F.; Kikidis, Dimitris; Lapira, Alec; Mazurek, Birgit; Norena, Arnaud; Rabau, Sarah; Lardinois, Rachelle; Cederroth, Christopher R.; Edvall, Niklas K.; Brueggemann, Petra G.; Rosing, Susanne N.; et al. (Frontiers in Psychology, 2017)
Background Though clinical guidelines for assessment and treatment of chronic subjective tinnitus do exist, a comprehensive review of those guidelines has not been performed. The objective of this review was to identify current clinical guidelines, and compare their recommendations for the assessment and treatment of subjective tinnitus in adults. Method We systematically searched a range of sources for clinical guidelines (as defined by the Institute of Medicine, United States) for the assessment and/or treatment of subjective tinnitus in adults. No restrictions on language or year of publication were applied to guidelines. Results Clinical guidelines from Denmark, Germany, Sweden, The Netherlands, and the United States were included in the review. There was a high level of consistency across the guidelines with regard to recommendations for audiometric assessment, physical examination, use of a validated questionnaire(s) to assess tinnitus related distress, and referral to a psychologist when required. Cognitive behavioural treatment for tinnitus related distress, use of hearing aids in instances of hearing loss and recommendations against the use of medicines were consistent across the included guidelines. Differences between the guidelines centred on the use of imaging in assessment procedures and sound therapy as a form of treatment for tinnitus distress respectively. Conclusion Given the level of commonality across tinnitus guidelines from different countries the development of a European guideline for the assessment and treatment of subjective tinnitus in adults seems feasible. This guideline would have the potential to benefit the large number of clinicians in countries where clinical guidelines do not yet exist, and would support standardisation of treatment for patients across Europe.